'Solomon': Terror and Terroir. Issue 2 (1st October 2014) - Mort, Graham
'Solomon' is a new work of short fiction, set in the United Kingdom and northern Uganda. It explores themes of memory, violence and recovery through the consciousness of a young Ugandan man. The accompanying essay '"Solomon": Terror and Terroir' reflects upon the genesis and writing of the story in the context of Terroir, a new book-length collection of fiction, with emphasis on depictions of violence and the relationship between the notion of terroir and human psychology.